Port Efficiency in APEC - Infante Jiménez, Zoe T.; Gutiérrez, Ariel (México y la Cuenca del Pacífico, 2015)
The main goal of this research is to identify and analyze factors that may significantly affect the levels of port efficiency in apec countries (particularly the infrastructural capacity). The assessment of such efficiency is a task that must play an important role in the management of ports in order to improve the possibility of development and success in commercial activities in their home countries. The competition among maritime ports is increasing continuously; the main purpose of such ports is to become the best option for companies to carry out their trading activities, particularly importing and exporting. Drawing on Data Envelopment Analysis, this paper develops a manner of assessing the comparative efficiency of ports. It applies this assessment method to a set of 33 ports in the apec trade alliance over a span of time from 2003-2010. The possibility of benchmarking the distinction of port efficiency in apec through this type of efficiency analyses will enhance and determine new methodological paths to achieve continuous improvement in the activities of maritime ports.